2002
DOI: 10.1097/01.asn.0000031803.55613.86
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Dissection of Increased Urinary Albumin Excretion in the Munich Wistar Fro[Combining Diaeresis]mter Rat

Abstract: Abstract. An elevated urinary albumin excretion (UAE) is a risk factor for the development of chronic nephropathy and for cardiovascular mortality. The Munich Wistar Frömter (MWF) rat represents a genetic model that develops spontaneously mild hypertension and a 142-fold increased UAE compared with normal Lewis rats at 14 wk of age. The genetic basis of UAE in male MWF was analyzed in relation to BP by using a quantitative trait (QTL) mapping strategy. F1-hybrids generated from a cross between MWF and Lewis ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
86
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(93 citation statements)
references
References 27 publications
6
86
1
Order By: Relevance
“…Based on the histological features of the FGS/Kist kidney, we here detected two QTLs for GSI, Gsi1&2, on Chrs 8 and 10. These QTLs were not homologous to those of the above rat models [2,4,19]. Thus, the FGS/Kist mouse may play an important role as a new source of QTLs to further FGS study.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…Based on the histological features of the FGS/Kist kidney, we here detected two QTLs for GSI, Gsi1&2, on Chrs 8 and 10. These QTLs were not homologous to those of the above rat models [2,4,19]. Thus, the FGS/Kist mouse may play an important role as a new source of QTLs to further FGS study.…”
Section: Discussionmentioning
confidence: 90%
“…In the fawn-hooded hypertensive rat, which develops severe renal damage with mild hypertension, a QTL for the degree of renal damage has been reported on Chr 1 [2], and a high susceptibility to renal damage has been observed in SHR rats carrying a segment of Chr 1 from Brown Norway rats [12]. More recently three QTLs explained increased urinary albumin excretion in the Munich Wistar Fromter rat, a model of chronic nephropathy [19]. These rat models have been studied for the genetic association between renal progression and hypertension.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Notably, these phenomena are more prominent in males than in females despite similar nephron deficit. Higher single nephron glomerular filtration rates and glomerular volume in males than females may contribute to this gender difference [33] (Table 1). …”
Section: Munich-wistar-fromter Ratmentioning
confidence: 99%
“…This locus accounts for approximately 30 to 40% of the urinary protein excretion (1). Studies in other rat models of renal failure have confirmed a role for the Rf-2 region in the development of UPV and UAV (33,28,38,29). In addition, Winn et al (37) have reported linkage to a familial form of focal segmental glomerulosclerosis (FGS) in a region of human chromosome 11 syntenic to Rf-2 in rat.…”
mentioning
confidence: 96%